Evaluating earthworms as candidates for remediating pesticide contaminated agricultural soil: A review - Mishra, C. S. K.; Samal, Suryasikha; Samal, Rashmi Rekha (Frontiers in Environmental Science, 2022)
Alterations of soil characteristics that result in reduction in ecosystem services invariably cause soil quality degradation.Such changes could be caused due to a variety of stressors,which might be physical,chemical,orbiologicalandcome from both anthropogenic and natural causes.Out of the wide variety of soil pollutants, agrochemicals contaminate soil biota the most.Numerous research' findings have confirmed that soil has been the most preferred site for the disposal of xenobiotics and therefore is likely to be the source of contamination for other natural resources like ground and surface waters.The ecological risk associated with contaminated soils depends on many physicochemical and biological processes that govern the transport and transformation of pesticides.Nevertheless,the persistence of pesticides in soil is a serious threat to both below and above-ground organisms which play key roles in sustaining soil functions.Oneof the viable methods to decontaminate soil is by utilizing living soil biota selectively. This process called bioremediation has traditionally been employed to remove chemical residues from soil or to lessen their toxicity levels. Although microbes have been extensively used for bioremediation, chemical breakdown and remediation are significantly aided by certain dominant soil fauna, such as earthworms. Since they modify soil quality,earthworms are regarded as soilengineers.Earthworms can participate in the degradation of pesticide residues, either directly through the release ofdetoxifying enzymes intheirgut orindirectly through their positiveinfluence onmicrobial populations which could degrade pesticides.The earthworm-supported pesticide degradation is largely confined to the gut microenvironment and the soil processed by the worms.The impact of earthworm species on pesticide degradation is widely variable which could be related to their feeding habits and microhabitats.Molecular docking studies have provided evidence in support of binding of organic molecules with agrochemicals.High level of organic matter in soil is expected to increase the binding of hydrophobic pesticides to organic ligands with consequent reduction in their bioavailability to microorganisms and increasing their persistence.Activities of earthworms is likely to induce growth of aerobic microbes capable of pesticide degradation.Among the various earthworm species,Lumbricus terrestris,PerionyxexcavatusandMetaphireposthuma have shown promising results as remediatingagents of pesticides contaminating farm soils.The present article focuses on the remediation process of hazardouspesticide-pollutedsoil using biologicalagent like earthworm.This approach may be both efficient and environmentallybeneficial